Analisis Skor APACHE II dalam Memprediksi Lama Rawat pada Pasien Kritis - Suryani Manurung, Kristina; Subandi, Andi; Sulistiawan, Andika; Irwanti Sari, Putri; Rudini, Dini (Pustaka Galeri Mandiri, 2025)
Critically ill patients treated in the Intensive Care Unit (ICU) and Intensive Cardiac Care Unit (ICCU) present varying levels of disease severity, which may influence length of stay. The APACHE II score is a widely used scoring system to assess the severity of illness in critically ill patients; however, data describing its association with length of stay at RSUD Raden Mattaher Jambi remain limited. This study aimed to analyze APACHE II scores and length of stay among critically ill patients in the ICU and ICCU. A descriptive quantitative study with a retrospective approach was conducted involving 83 adult critically ill patients treated between January and December 2023. Data were obtained from medical records, and APACHE II scores were calculated using the MDCalc application based on physiological parameters recorded within the first 24 hours of admission. Data analysis was performed using descriptive statistics. The results showed a mean APACHE II score of 16.37±6.68, with a range of 4–31, while the mean length of stay was 3.55±3.29 days, ranging from 1 to 20 days. The longest average length of stay was observed in patients with APACHE II scores of 11 and 12, and no consistent increase in length of stay was found with higher APACHE II scores. Variations in length of stay were also observed across individual physiological parameters of the APACHE II score. In conclusion, APACHE II scores among critically ill patients were predominantly in the moderate to severe category with relatively short lengths of stay, and APACHE II cannot be used as a single predictor of length of stay without considering other clinical factors.